Modeling of adsorption of toxic chromium on natural and surface modified lightweight expanded clay aggregate (LECA) - Kalhori, Ebrahim Mohammadi; Yetilmezsoy, Kaan; Uygur, Nihan; Zarrabi, Mansur; Abu Shmeis, Reham M. (ELSEVIER, 2013)
Lightweight Expanded Clay Aggregate (LECA) modified with an aqueous solution of magnesium chloride MgCI2 and hydrogen peroxide H2O2 was used to remove Cr(VI) from aqueous solutions. The adsorption properties of the used adsorbents were investigated through batch studies, Scanning Electron Microscopy (SEM), X-ray Diffraction (XRD), X-ray Fluorescence Spectroscopy (XRF), and Fourier Transform Infrared (FTIR) spectroscopy. The effect created by magnesium chloride on the modification of the LECA surface was greater than that of hydrogen peroxide solution and showed a substantial increase in the specific surface area which has a value of 76.12 m(2)/g for magnesium chloride modified LECA while the values of 53.72 m(2)/g, and 11.53 m(2)/g were found for hydrogen peroxide modified LECA and natural LECA, respectively. The extent of surface modification with enhanced porosity in modified LECA was apparent from the recorded SEM patterns. XRD and FTIR studies of themodified LECA surface did not show any structural distortion. The adsorption kinetics was found to follow the modified Freundlich kinetic model and the equilibrium data fitted the Sips and Dubinin-Radushkevich equations better than other models. Maximum sorption capacities were found to be 198.39, 218.29 and 236.24 mg/g for natural LECA, surface modified LECA with H2O2 and surface modified LECA with MgCI2, respectively. Adsorbents were found to have only a weak effect on conductivity and turbidity of aqueous solutions. Spent natural and surface modified LECA with MgCI2 was best regenerated with HCI solution, while LECA surface modified with H2O2 was best regenerated with HNO3 concentrated solution. Thermal method showed a lower regeneration percentage for all spent adsorbents. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Batch system; Chromium; Isotherm; Kinetic; Lightweight expanded clay aggregate (LECA); HEXAVALENT CHROMIUM; AQUEOUS-SOLUTION; REMOVAL; SORPTION; MONTMORILLONITE; KINETICS; CADMIUM; EQUILIBRIUM; ZEOLITE; CR(VI); Chemistry; Materials Science; Physics